A study on variability of bioactive proteins in camel (Camelus dromedarius) milk: Insulin, insulin‐like growth factors, lactoferrin, immunoglobulin G, peptidoglycan recognition protein‐1, lysozyme and lactoperoxidase. (9th December 2021) - Mohamed, Huda; Ranasinghe, Meththa; Amir, Naheed; Nagy, Peter; Gariballa, Salah; Adem, Abdu; Kamal‐Eldin, Afaf
Abstract : Milk samples were collected from 140 individual dromedary camels ( Camelus dromedarius ) to determine the variability in the concentrations of several bioactive whey proteins. The ranges were as follows: insulin (IN) (17.8–51.1 mIU/L), insulin‐like growth factor I (IGF1) (1.4–736.1 ng/mL), insulin‐like growth factor II (IGF2) (13.7–82.6 ng/mL), lactoferrin (639.4–2094.9 µg/mL), immunoglobulin G (IgG) (7.3–17.9 mg/mL), peptidoglycan recognition protein‐1 (PGRP‐1) (1.6–22.3 ng/mL), lysozyme (LZ) (23.3–71.4 µg/mL) and lactoperoxidase (LPO) (7.1–15.5 ng/mL). These data demonstrate wide variation in the concentrations of the studied proteins. Significant correlations ( P  < 0.05) were observed between the concentrations of IN and LZ, IN and IgG, IN and PGRP‐1, LZ and PGRP‐1, IgG and LPO, and IgG and PGRP‐1. Abstract : Variability of bioactive whey proteins in Dromedary camel milk samples collected from individual animals.